The Influence of Social Capital, Commitment, Justice, Employee Status, Age, Gender, and Community Health Center Strata on Performance at the Metro, Lampung, Indonesia - Umar, Alwan Dhafi; Tamtomo, Didik Gunawan; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2025)
Background: The performance of health workers is one of the biggest reasons for the good health services. Various factors affect employee performance such as commitment, employee status, justice and social capital. This study aims to see the influence of social capital along with other accompanying factors such as justice, organizational commitment, employee status, and strata of the Health Center on the performance of Health Center employees. Subjects and Method: This study is an observational analytical study with a cross-sectional design. This research was conducted on 11 health centers in Metro City, Lampung, Indonesia in April - May 2024. A sample of 200 health center employees was selected by simple random sampling. The dependent variable in this study is the performance of health center employees. The independent variables in the study were social capital, fairness, organizational commitment, employee status, health center strata, age, and gender. Data collection was carried out using a questionnaire and analyzed by multiple linear regression. Results: Social capital (b= 0.07; CI 95%= 0.06 to 0.14; p= 0.048), justice (b= 0.13; CI 95%= 0.06 to 0.20; p= <0.001), organizational commitment (b= 0.10; CI 95%= 0.02 to 0.17; p= 0.012), and the strata of the Health Center (b= 1.01; CI 95%= 0.62 to 1.41; p= <0.001) has an influence on improving performance and is statistically significant. Officer status (b= -0.28; CI 95%= -0.56 to -0.01; p= 0.038) had a degrading effect and was statistically significant. Age (b= -0.13; CI 95%= -0.39 to 0.11; p= 0.284) and gender (b= 0.06; CI 95%= -0.35 to 0.11; p= 0.750) has no significant effect on performance. Conclusion: The performance of health center employees is influenced by social capital, justice, organizational commitment, strata, and employee status. Age and gender are not factors that affect performance.